A study to assess the effect of planned health teaching regarding antenatal exercises among antenatal mothers attending antenatal clinic in selected hospitals Pimpri, Pune City. - Satish Weljale, Bharati (International Journal of Nursing Research, 2023)
Aim: The study was to assess effectiveness of planned teaching regarding antenatal exercises among antenatal mothers. Material and methods: Purposive sampling method was used to select 100 antenatal mothers. A structured questionnaire was prepared for assessing the knowledge of the antenatal mothers. The tool consisted of three sections. Section- I included items seeking information on demographic profile, Section- II includes overall knowledge regarding antenatal exercises and Section-III included items to assess knowledge of antenatal mothers regarding selected antenatal exercises. The reliability coefficient was calculated with the help of ‘rational equivalence’ method and the value is equal to 0.89. As the value of (r11) in this study is 0.89, so the test is reliable. The chi-square test is implemented in study. Results: Section-I shown that characteristics of samples, most of the samples (59%) were in the age group of 21–25 yrs and very few (2%) were in the age group of 30–35yrs. Majority of the antenatal mothers (50%) were secondary and very few (3%) were post graduate. Most of the samples (54%) were in service and very few (3%) were into business. Most of the samples (48%) were having monthly income in Rs. 5,000 – 10,000 and very few (1%) below Rs. 5000. Most of the samples (44%) were P1, 39% were Primigravida and very few (4%) were P3. Almost same percentage of the mothers belongs to both nuclear as well as joint family. Results of section-II shows that most (64%) of the samples knew about the antenatal exercises that are during pregnancy but very few (11%) knew how to perform the antenatal exercises and (14%) knew about the benefits of antenatal exercises. After the planned teaching there is significant improvement in the knowledge. During pregnancy 38% samples had backache and 35% samples had leg cramps. Results of section-III shows that 44% mothers knew the information of antenatal exercises. Advantages of antenatal exercises knew by 45.5% mothers. The types of antenatal exercises knew by 42.5% mothers. The precautions to be taken during antenatal exercises knew by 42.5% mothers. The finding shows that the mean knowledge scores about antenatal exercises obtained from mothers in pretest was 4.43 and in post-test 16.98. Conclusion: The planned teaching regarding antenatal exercises is effective.